Efektifitas Bimbingan Kelompok Menggunakan Teknik Outbound Untuk Mengurangi Kejenuhan Belajar Mahasiswa - Yansen Alberth Reba; Densemina Yunita Wabdaron (Universitas Nusantara PGRI Kediri, 2025)
This study aims to examine the effectiveness of group guidance using the outbound technique in reducing students’ learning fatigue. The background of this research is based on the high level of learning fatigue, characterized by mental exhaustion, emotional exhaustion, and feelings of ineffectiveness in academic activities. The study employed a pre-experimental design with a one-group pretest-posttest model, involving 19 students from the Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Cenderawasih University, who were selected through purposive sampling. The research instrument was a learning fatigue scale consisting of three main indicators. The results showed that the average pre-test score was 65.20 (high category) and the post-test score was 43.10 (moderate category). The paired sample t-test yielded a t-value of -6.342 with a significance level of 0.000 < 0.05, indicating a significant difference. Therefore, it can be concluded that group guidance using the outbound technique is effective in reducing students’ learning fatigue.